2016
DOI: 10.1063/1.4961429
|View full text |Cite
|
Sign up to set email alerts
|

Short-pulse amplification by strongly coupled stimulated Brillouin scattering

Abstract: We examine the feasibility of strongly-coupled stimulated Brillouin scattering as a mechanism for the plasma-based amplification of sub-picosecond pulses. In particular, we use fluid theory and particle-in-cell simulations to compare the relative advantages of Raman and Brillouin amplification over a broad range of achievable parameters.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…The linear growth rate of the undamped system represents the early-time behavior of the interaction and is important for quantifying the highest degree of amplification that may be expected. It can be shown that the undamped asymptotic seed growth rate in the linear regime is simply the instability plane-wave growth rate, for which expressions are well known for SRS, WC-SBS, and SC-SBS and which may be readily calculated for in-termediate SBS conditions [37]. In Fig.…”
Section: Appendix D: Numerical Solutions To the Coupling Equationsmentioning
confidence: 93%
See 4 more Smart Citations
“…The linear growth rate of the undamped system represents the early-time behavior of the interaction and is important for quantifying the highest degree of amplification that may be expected. It can be shown that the undamped asymptotic seed growth rate in the linear regime is simply the instability plane-wave growth rate, for which expressions are well known for SRS, WC-SBS, and SC-SBS and which may be readily calculated for in-termediate SBS conditions [37]. In Fig.…”
Section: Appendix D: Numerical Solutions To the Coupling Equationsmentioning
confidence: 93%
“…(a * 1 a 2 ) (A13) which reduces to the strongly-coupled and weaklycoupled limits, as described in Ref. [37], if the secondorder or first-order time derivatives are neglected, respectively.…”
Section: Appendix A: Derivation Of the Three-wave Coupling Equationsmentioning
confidence: 99%
See 3 more Smart Citations